Factors Affecting Tourists' Interest in Returning (Case Study: Likupang Super Priority Destinations) - Chrisna Riane Opod; Grace Christin Sumakul; Irvandi Waraney Ombuh; Vica Wilani Kaparang (PT FORMOSA CENDEKIA GLOBAL, 2023)
Super Priority Destinations (DSP) are one of the efforts of the Government of Indonesia through the Ministry of Tourism and Creative Economy to increase tourism in Indonesia. One of the DSPs is Likupang in North Minahasa Regency. Revisit Intention is the main goal of tourism managers. The purpose of this research is to look at the factors that influence Revisit Intention at the Likupang DSP. From the results of multiple regression analysis, it is obtained that Customer Experience and Social Media Marketing have a significant influence on Revisit Intention. Tourism managers, in this case the Provincial and Regency Governments and related agencies, need to pay attention to the experiences that can be obtained by tourists, as well as maximize Social Media as an effective marketing tool to increase Revisit Intention to Likupang Super Priority Destinations.